Patent foramen ovale closure vs. medical therapy alone after cryptogenic stroke in China: A cost-effectiveness analysis - Wei, Na; Liu, Bo; Ma, Meijuan; Zhang, Xuejun; Zhang, Wei; Hou, Fangxia; Liu, Fuqiang; Yu, Xiangyou (Frontiers in Public Health, 2022)
Background: In 2019, there were 28.76 million patients with stroke in China, of which cryptogenic stroke (CS) accounted for approximately 25%. Patent foramen ovale (PFO) is related to CS, and PFO closure can reduce recurrent stroke. To date, no study has investigated the cost-effectiveness of PFO closure versus medical therapy among such populations in China. Methods: A Markov model with a cycle length of three months was established to compare the 30-year cost-effectiveness of PFO closure and medical therapy. The transition probability of recurrent stroke was derived from the RESPECT study, and the costs and utility were obtained from domestic data or studies conducted in China. The primary outcome of this study was the incremental cost-effectiveness ratio (ICER), which represents the incremental cost per quality-adjusted life year (QALY). PFO closure was considered cost-effective if the ICER obtained was lower than the willingness-to-pay (WTP) threshold of 37654 USD/QALY; otherwise, PFO closure would be regarded as not cost-effective. One-way and probabilistic sensitivity analyses were performed to test the robustness of the results. Results: After a simulation of a 30-year horizon, a cryptogenic stroke patient with PFO is expected to have 13.15 QALY (15.26 LY) if he receives PFO closure and a corresponding value of 11.74 QALY (15.14 LY) if he receives medical therapy. The corresponding costs in both cohorts are 8131 USD and 4186 USD, respectively. An ICER of 2783 USD/QALY and 31264 USD/LY was obtained, which is lower than the WTP threshold. One-way sensitivity analysis and probabilistic sensitivity analysis showed that the results were robust. Conclusion: With respect to the WTP threshold of three times per capita GDP in China in 2021, PFO closure is a cost-effective method for Chinese cryptogenic stroke patients with PFO, as we have shown in a 30-year simulation.